Factors Affecting Employee Achievements At Bank Mandiri Persero Medan Kredit Card Unit Region I - Christine Caroline Pangaribuan; Yeni Absah; Rulianda Purnomo Wibowo (UNIVED Press, 2024)
The purpose of this study is to identify and evaluate the impact of Bank Mandiri Persero Medan Credit Card Unit Region I / Sumatra 1 management skills on employee achievements using employee participation as an intervening variable. This study only examined employees of Bank Mandiri Persero Medan Credit Card Region Unit. Sumatra has 1 to 60 employees. The census sampling strategy uses a comprehensive sample size of 60 people to observe each member of the population. The research instrument was a questionnaire. In this study, hypotheses were evaluated using path analysis. The results show that management skills at Bank Mandiri Persero Medan Credit Card Unit Region I/Sumatra 1 had a positive and significant impact on employee participation. Bank Mandiri Persero Medan Credit Card Unit Region I / Sumatra 1's employee achievements was positively influenced by management skills and employee participation. Management skills has a significant and positive impact on employee participation at Bank Mandiri Persero Medan Credit Card Unit Region I / Sumatra 1.